The role of dogs in maintaining health and quality of life - Szabolcs TÓTH; Antonia KINCZEL; Attila LENGYEL; Réka PÁLINKÁS; Anikó MOLNÁR; Antal Lovas KISS; Peter ZIDEK; Anetta MÜLLER (Editura Universităţii din Oradea, 2023)
Dogs, as companion animals, have many positive effects on the health and quality of life of dog owners, if the purpose of dog ownership is not as a watchdog but as a companion animal. Dogs can encourage the owner to engage in daily walks, play, sports and other interactions, which are beneficial for physical, mental and social well-being, as has been proven by various studies. The aim of our research was to investigate the role and impact of dogs on dog owners' physical activity, dog interactions and mental health. To achieve our goal, we created an online questionnaire that was completed by 220 dog owner respondents. Our research sought to understand how dog owners develop a relationship with their companion animal, the role of the dog in their active leisure time and the impact of the dog on the owner's mental health. We used a four-part questionnaire to obtain our answers. The first part covered demographic questions, the second part focused on the respondent's dog and the time spent with him/her doing sports. In the third part, the Monash Dog-Owner (MDORS) (Cavo et al., 2016) questionnaire was used and in the last part, the Mental Health Test was used. Our research has confirmed that exercising with dogs has positive effects on humans. Walking with a dog encourages exercise and also encourages the owner to spend time outdoors. Around 26% of the people in the study exercise together and 77.3% walk with their dog. The mental health of dog owners is medium and the level of happiness is above average. These results confirm that promoting dog ownership can help to achieve the objectives of public health strategies to encourage people to be more active, to exercise or to improve quality of life and health.